OPAL: a randomised, placebo-controlled trial of opioid analgesia for the reduction of pain severity in people with acute spinal pain. Trial protocol - Lin, Chung-Wei Christine (BMJ Open, 2016)
INTRODUCTION: Low back pain and neck pain are extremely prevalent and are responsible for an enormous burden of disease globally. Strong analgesics, such as opioid analgesics, are recommended by clinical guidelines for people with acute low back pain or neck pain who are slow to recover and require more pain relief. Opioid analgesics are widely and increasingly used, but there are no strong efficacy data supporting the use of opioid analgesics for acute low back pain or neck pain. Concerns regarding opioid use are further heightened by the risks of adverse events, some of which can be serious (eg, dependency, misuse and overdose). METHODS AND ANALYSIS: OPAL is a randomised, placebo-controlled, triple-blinded trial that will investigate the judicious use of an opioid analgesic in 346 participants with acute low back pain and/or neck pain who are slow to recover. Participants will be recruited from general practice and randomised to receive the opioid analgesic (controlled release oxycodone plus naloxone up to 20 mg per day) or placebo in addition to guideline-based care (eg, reassurance and advice of staying active) for up to 6 weeks. Participants will be followed-up for 3 months for effectiveness outcomes. The primary outcome will be pain severity. Secondary outcomes will include physical functioning and time to recovery. Medication-related adverse events will be assessed and a cost-effectiveness analysis will be conducted. We will additionally assess long-term use and risk of misuse of opioid analgesics for up to 12 months. ETHICS AND DISSEMINATION: Ethical approval has been obtained. Trial results will be disseminated by publications and conference presentations, and via the media. TRIAL REGISTRATION NUMBER: ACTRN12615000775516: Pre-results.